Determinants of Dividend Per Share in Indonesia’s Non-Cyclical Manufacturing Firms - Anditha Novriani; Suhula Divina Marom; Farah Margaretha Leon (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study investigates the influence of internal firm-specific variables on dividend per share (DPS) within the non-cyclical manufacturing sector in Indonesia. It emphasizes key internal determinants that shape corporate dividend policy.Method: A quantitative research design is employed, utilizing panel data regression on a sample of 26 non-cyclical manufacturing firms listed on the Indonesia Stock Exchange over the period 2021–2024. Secondary data are obtained from audited annual financial reports. The fixed-effects model is selected as the most appropriate estimation technique, based on the results of the Chow and Hausman specification tests, to ensure model robustness and accuracy.Result: Empirical analysis reveals that firm life cycle, leverage, firm size, firm age, and earnings volatility exert a statistically significant influence on DPS. Conversely, profitability, liquidity, and growth opportunities are found to have no significant effect.Practical Implications for Economic Growth and Development: The findings have important implications for corporate managers, investors, and policymakers in formulating dividend strategies that align with a firm’s financial structure and stage of development. Enhanced dividend decision-making can strengthen investor confidence, improve firm valuation, and promote capital market efficiency, thereby contributing to sustainable economic development.Originality/Value: This study extends the existing body of knowledge by integrating earnings volatility into the analysis of dividend determinants, offering original empirical evidence from the Indonesian manufacturing sector. The results provide a deeper understanding of firm-level financial factors influencing dividend policy in the context of emerging economies.